An atomistic modeling framework for valence change memory cells. (January 2023) - Kaniselvan, Manasa; Luisier, Mathieu; Mladenović, Marko
Abstract: We present a framework dedicated to modeling the resistive switching operation of Valence Change Memory (VCM) cells. The method combines an atomistic description of the device structure, a Kinetic Monte Carlo (KMC) model for the creation and diffusion of oxygen vacancies in the central oxide under an external field, and an ab initio quantum transport method to calculate electrical current and conductance. As such, it reproduces a realistically stochastic device operation and its impact on the resulting conductance. We demonstrate this framework by simulating a switching cycle for a TiN/HfO 2 /TiN VCM cell, and see a clear current hysteresis between high/low resistance states, with a conductance ratio of one order of magnitude. Additionally, we observe that the changes in conductance originate from the creation and recombination of vacancies near the active electrode, effectively modulating a tunneling gap for the current. This framework can be used to further investigate the mechanisms behind resistive switching at an atomistic scale and optimize VCM material stacks and geometries. Highlights: We develop a framework to model resistive switching in Valence Change Memory (VCM) at an atomistic resolution. The method combines stochastic Kinetic Monte Carlo simulations with a Quantum Transport solver. Simulation results reveal a tunneling-gap-mediated switching mechanism between low- and high-resistance states.